Uji Daya Hambat Ekstrak Etanol Kulit Jeruk Nipis (Citrus aurantifolia (Christm.) Swingle) Sebagai Antibakteri Terhadap Escherichia coli - S, Mahral Effendi (Herbal Medicine Journal, 2021)
Diarrhea is one of the public health problems and is a major cause of morbidity and mortality in infants and children. One of the main causes of diarrhea is due to Escherichia coli bacterial infection. Medicinal plants are currently widely used by the community as an alternative treatment because the ingredients are easy to obtain, the price is relatively cheap and the side effects are relatively low compared to synthesized drugs such as lime (Citrus aurantifolia (Christm.) Swingle). The purpose of this study was to determine the effect of ethanol extract of lime peel (Citrus aurantifolia (Christm.) Swingle) on the growth of Escherichia coli bacteria and to determine the potential of ethanol extract of lime peel (Citrus aurantifolia (Christm.) Swingle) as an antibacterial and antibacterial cause of diarrhea. The extraction method with maceration using 96% ethanol solvent, while the antibacterial activity test was carried out using the paper disc diffusion method. The results showed that the ethanol extract of lime peel at concentrations of 10%, 30%, 50% and 70% had inhibition zone diameters of 7.30 mm, 7.48 mm. 8.71 mm and 12.80 mm respectively. The conclusion of this study is that the ethanol extract of lime peel is effective at a concentration of 70% with a strong category.